School Without Classroom: An Experimental Study Of The Horizontal Education Model In An Alternative Learning Community - Amalia Tasya (PT. Anagata Sembagi Education, 2025)
This study aims to explore the effectiveness of the horizontal education model in alternative learning communities, focusing on the implementation of the